Photonica: Growing a Spin-Out - Cross, Adam; Handscombe, Bob (Senate Hall, 2004)
This case invites students to consider the challenges associated with establishing and growing an entrepreneurial, technology-driven, university 'spin-out' firm. Drawing heavily, though by no means exclusively, on the real-world experiences of Stress Photonics, the case examines the performance and activities of the fictitious firm, Photonica, from the perspective of its two principle founders, Bob and Jake. Students are encouraged to consider key features in Photonica's evolution, including the role of the University of Wisconsin in its establishment and development, how it created and exploited new technologies, the importance of its key clients and alliance partners, and the critical role of the US Small Business Innovation Research Program (SBIR) in promoting enterprise in Photonica and more widely across the USA. Students are invited to present a five year strategic plan for the company.
Keywords: university ‘spin-out’|product development strategy|management and control in small and medium-sized enterprises (SMEs)|growing an SME|university research parks|the US Small Business Innovation Research Program (SBIR)